Verification of the Z-Component in the RTK Survey of Drogden Channel - Eeg, Jørgen (The International Hydrographic Review, 2004)
The object of this investigation is to detect the presence of long-term blunders in the vertical component of a hydrographic survey, as e.g. cycle slips in the real-time kinematic GPS system or biases in the tide correction of the tracks. To this end the paper proceeds along two tracks: A visual, subjective one, where the contributions of a track to a DTM is inspected interactively, and an objective one, based on the method of least squares, where the tracks of the survey are construed as nodes· in a leveling network.